Assessment of the DPP‐IV inhibitory activity of a novel octapeptide derived from rapeseed using Caco‐2 cell monolayers and molecular docking analysis. Issue 10 (30th July 2020) - Xu, Feiran; Mejia, Elvira Gonzalez de; Chen, Hong; Rebecca, Kowalski; Pan, Mengmeng; He, Rong; Yao, Yijun; Wang, Lifeng; Ju, Xingrong
Abstract: The Octapeptide ELHQEEPL, which was identified from the rapeseed protein napin showed prominent Dipeptidyl peptidase‐IV (DPP‐IV) inhibitory activity. The objective of this study was to investigate the DPP‐IV inhibitory activity and transepithelial transport of ELHQEEPL in an approaching intestinal condition using Caco‐2 cell monolayers. ELHQEEPL and its degraded fragments EL, HQEEP, and methylated ELHQEEPL were transported across Caco‐2 cell monolayers through different pathways. Compared with the nonbiological enzyme inhibition test, the in vitro experiment on Caco‐2 cell monolayers showed that the IC50 value of DPP‐IV inhibition increased by 43.11% for ELHQEEPL. There was no significant change in DPP‐IV gene expression in the Caco‐2 cell monolayers upon treatment with ELHQEEPL. Furthermore, molecular docking predicted that the weaker binding between inhibitory peptide and enzyme for the degradation products from ELHQEEPL during transepithelial transport greatly limited its role in inhibiting DPP‐IV. Practical applications: The DPP‐IV inhibitory activity of ELHQEEPL was confirmed using Caco‐2 cell monolayers as a novel assessment tool, although its potency was reduced by metabolic degradation. In general, this study reported the use of Caco‐2 cell monolayers as a tool for comprehensively studying peptides as sources of DPP‐IV inhibitors. A Caco‐2 cell‐based approach with molecular docking can be adapted for the investigation of intestinal absorption and activity attenuation of food peptides being considered for enzymatic action. Moreover, since the Caco‐2 cells express a wide range of enzymes, this method can be used for screening for other active food peptides such as for the inhibitors of ACE and a‐glucosidase. Abstract : ELHQEEPL and its three degraded fragments were transported across Caco‐2 cell monolayers through different pathways. The weaker binding between inhibitory peptide and enzyme for the degradation products from ELHQEEPL greatly limited its role in inhibiting DPP‐IV, such as IC50 . There was no significant change in DPP‐IV gene expression in the Caco‐2 cell monolayers upon treatment with ELHQEEPL.